The Human Resources Department as An Instrument of Corporate Legal Compliance - Ni Putu Ega Maha Wiryanthi; Luh Putu Yeyen Karista Putri (Indonesian Journal of Law and Islamic Law (IJLIL), 2026)
This article examines the legal issue of repositioning the Human Resources Department (HRD) as an operational instrument of corporate legal compliance in employment governance. The central problem is how HRD can translate labour law obligations into daily work processes that produce valid, traceable, and auditable evidence of compliance, particularly to prevent employment disputes, administrative sanctions, and corporate liability. This study uses normative/doctrinal legal research based on primary and secondary legal materials. The analysis applies statutory and conceptual approaches, supported by legal entity theory, legal compliance theory, Good Corporate Governance principles, and the Three Lines of Defence framework, with a limited comparative reference to Singapore’s employment fairness regulation. The findings show that many HRD activities, including recruitment, employment contracts, wages, working hours, social security, occupational safety and health, discipline, and termination, have direct legal consequences and must therefore be managed as compliance-control processes. The study also finds that labour compliance cannot rely on administrative checklists alone because compliance must be evidenced through systematic documentation, record management, audit trails, monitoring, and independent assurance. The novelty of this article lies in formulating the HR Legal Compliance Cycle, a norm–process–evidence model that positions HRD as the first-line process owner and producer of compliance evidence, while legal, risk, compliance, and internal audit units function as review and assurance mechanisms. This model contributes to corporate governance scholarship by integrating employment law, compliance control, evidentiary readiness, and operational accountability into a single framework.